2019
DOI: 10.3400/avd.cr.18-00125
|View full text |Cite
|
Sign up to set email alerts
|

A Ruptured Popliteal Artery Aneurysm Treated with Coil Embolization

Abstract: A popliteal artery aneurysm is one of the most common peripheral arterial aneurysms. These aneurysms can cause distal embolization and thrombosis, leading to limb loss. However, their rupture is unusual. Here we report a case in which a popliteal aneurysm with chronic occlusion at its outflow artery developed a nonfatal, painful rupture. We performed only coil embolization of the proximal artery, and the aneurysm was successfully excluded. After the procedure, collateral circulation was maintained. No ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…3 Although open surgery remains the first-line treatment for infected rPAA, 2,3 endovascular repair has strong benefit in emergency cases or high-risk surgical patients. 4,5,6,7 In this case, technically challenging endovascular exclusion performed via retrograde approach, followed by wire snaring and antegrade endograft deployment. The antegrade wiring through the ruptured aneurysm and compressed distal segment is sometimes challenging.…”
Section: Discussionmentioning
confidence: 93%
“…3 Although open surgery remains the first-line treatment for infected rPAA, 2,3 endovascular repair has strong benefit in emergency cases or high-risk surgical patients. 4,5,6,7 In this case, technically challenging endovascular exclusion performed via retrograde approach, followed by wire snaring and antegrade endograft deployment. The antegrade wiring through the ruptured aneurysm and compressed distal segment is sometimes challenging.…”
Section: Discussionmentioning
confidence: 93%
“…A literature review conducted at the time of submission of this case report showed 62 [2][3][4][5][6][7][8][9][10][11][12][13] reported cases of ruptured PAA. Most cases reported were males, with an age range of 55-96 and a mean age of 81.…”
Section: Discussionmentioning
confidence: 99%
“…Different treatment modalities were used to treat such cases; however, the majority of the patients were treated with a standard open repair with exclusion of the aneurysm and bypass surgery. Only one case was treated with coil embolization [10], and twelve were treated by endovascular intervention [2-5, 7, 11-13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation